Medieval and Modern Civil Wars
1 online resource.
Keywords: Most medieval historians have explained the 'civil wars' in Scandinavia in the 12th and 13th centuries as internal conflicts within a predominantly national and implicitly state-centered politico-constitutional framework. This book argues that the conflicts during this period should be viewed as less disruptive, less internal and less state-centered than in previous research. It does so through six articles comparing the civil wars in Scandinavia with civil wars in Afghanistan and Guinea-Bissau in the last decades, applying theories and perspectives from anthropology and political science. Finally, four articles discuss civil wars in a broader perspective. Contributors are Ebrahim Afsah, Gerd Althoff, Jenny Benham, John Comaroff, Hans Jacob Orning, Frederik Rosén, Jón Viðar Sigurðsson, Henrik Vigh, Helle Vogt, Stephen D. White, and Øyvind Østerud.